Effects of Operating Conditions on the Flow in the Moving Blade Passage of a Single Stage Axial-Flow Fan - Tsutomu Adachi; Yutaka Yamashita; Kennichiro Yasuhara; Tatsuo Kawai (International Journal of Rotating Machinery)
Three dimensional steady and unsteady velocity distributions in the axial flow fan were measured using a hot wire probe for various operational conditions, various rotational speeds and various measuring positions. For measuring the velocity distributions in the blade passage, a specially designed and manufactured hot wire traversing apparatus was used. Steady velocity distributions, turning angles, effects of incident to the cascade, flow leakage through the tip clearance and effects of the flow separation show the flow phenomena through the blade passages. Unsteady velocity distributions show time dependent procedures of the wake flowing through the moving blade passage. Considering these results of measurements, the effects of the upstream stationary blade and the effects of Reynolds number on the flow were considered.